Penerapan sistem agroforestri kopi pada petani di Kabupaten Bener Meriah, Aceh, Indonesia - Arrayyan Najla; Munzilin Munzilin; Nazwa Nazwa; Nova Fajarna; Raihana Putri Salsabila; Risnelli Risnelli; Vania Fachreyna Morhaban; Wiga Tiara; Cut Hudia Amaliana; Rosi Wahyuni (Universitas Syiah Kuala, 2025)
Bener Meriah Regency, Aceh, is one of the main coffee production centers in Indonesia with great potential for sustainable agricultural development. This study was conducted with the aim of analyzing the implementation of the coffee agroforestry system by farmers, identifying the benefits and challenges faced, and providing strategic recommendations to support the broader application of this agroforestry system. The research method used was a descriptive qualitative approach. The results of the study showed that the coffee agroforestry system has been applied by farmers for more than five years, involving various companion plants such as avocado and shade trees such as Leucaena. This agroforestry system has proven to provide economic benefits through crop diversification, as well as ecological benefits. Therefore, it is necessary to enhance farmers’ capacity, provide production facilities, and implement policy interventions to strengthen the adoption of coffee agroforestry as a model of sustainable agriculture in the region.